PENGEMBANGAN SOAL PEMECAHAN MASALAH BERBASIS SELF REGULATED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI USAHA DAN ENERGI - Itta Ma'ul Hayat; Edy Tandililing; Erwina Oktavianty (Universitas Tanjungpura, 2022)
This study aims to determine the prototype, the feasibility of the questions, the ability to solve questions based on self-regulated learning on the learning outcomes of students in the business and energy materials. The prototype is used as a reference in developing problem solving problems based on self regulated learning. The development model used is a combination of the Brog and Gall development research steps and the Dick and Carey development model design. The prototype questions include scoring guidelines, answer keys and a grid of questions containing: 1) core competencies, 2) basic competencies, 3) question indicators, 4) cognitive level, 5) questions. The result of this problem design is called a prototype. The feasibility of the question is whether it is feasible or not seen from the results of validation by experts for use in this study. The comparison of the results of the trials carried out got the average value of the small group trial, which obtained 86.66 results, the medium group trial obtained the results of 91.66, and the large group trial obtained the results of 93.45. From the results obtained, the value exceeds the minimum completeness criteria (KKM).